Streptococcus mutans – Retrieved or Vanished - Jyoti Sharma; Deepanshu Sharma (Journal of Primary Care Dentistry and Oral Health)
Background: Initial caries development in the form of white spot lesions (WSLs) on the labial surfaces is a serious side effect of orthodontic treatment with fixed appliances. The irregular surfaces of brackets, bands, and wires limit the naturally occurring self-cleansing mechanism of the oral musculature and saliva. Over time, the colonization of aciduric bacteria (Streptococcus mutans) results in active caries lesions. Patients with fixed appliances experience an increased incidence of gingivitis during treatment. Aim: (1) To know the S. mutans count in the saliva of children before application (control) to immediately after application, 1 month, 3 months, and 6 months after application of pit and fissure sealant and fluoride application. (2) To evaluate and compare the effects of pit and fissure sealant and fluoride therapy on WSLs in orthodontic patients. (3) To know the periodontal index and calculus index before application (control) to immediately after application, 1 month, 3 months, and 6 months after application of pit and fissure sealant and fluoride application. Materials and Methods: A total of 10 patients were 12–14 years old and had orthodontic treatment. Caries risk assessment was done for each patient. Periodontal and calculus index were done for each patient for 6 months. S. mutans counts were cultured on Mitis Salivarius plates and colony counts of S. mutans were recorded. Reduction in S. mutans count for study was observed in all the cases and the effectiveness of these pit and fissure sealants were comparable. Results: A study on oral hygiene practice among 10 children showed diverse habits. The S. mutans counts were measured at baseline, after 1 h of treatment, at 1 month, 3 months, and 6 months follow-up using colony-forming units per milliliter. Before treatment, the mean number of S. mutans was 2.5 ± 0.52. This number decreased to 2.0 ± 0.66 after 1 h of treatment, further reduction was observed at 1 month (1.4 ± 0.51), 3 months (1.40 ± 0.51), and 6 months (1.20 ± 0.42). Conclusion: After applying acidulated phosphate fluoride and pit and fissure sealant for 1 h, 1 month, and 3 to 6 months, there was a statistically significant decrease in the S. mutans count in saliva as compared with the baseline.